Analisa Tahanan Dan Daya Mesin Pada Kapal Mini LNG Berbasis Simulasi Numerik - Kusnindar Priohutomo; Endah Suwarni; Cakra Wijaya (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
The demand for small LNG carriers in Indonesia is increasing along with the increasing demand for LNG supply from the LNG field to the islands in eastern Indonesia. The distribution of LNG to islands in eastern Indonesia is not efficient if using a larger LNG carrier because in the islands there is no gas pipeline infrastructure to distribute LNG from the LNG terminal at the port to the user. With a small LNG carrier, the distribution LNG can use a small LNG tank that will be taken by land vehicles after the ship rests at the port. To design a small LNG ship, various calculations are needed so that the ship being built will have a good and efficient performance. One of them that must be calculated is the ship's resistance and engine power to be installed. In this paper the prediction of ship resistance and EHP BHP for prediction power of engine using numerical simulation methods. The results of this paper are for ship resistance at design 1 of 101.01 kN and for design 2 of 267.06 kN. In design 1 for EHP of 519.93 kW and BHP of 611.68 kW, and in design 2 EHP of 1373.87 kW and BHP of 1616.33 kW.